Association between eating pattern and food neophobia in children with Autism Spectrum Disorder (ASD): Parents' perceptions - Roosje R. Oewen; Witriana Latifa; Rini Triani; Ika Anisyah; Syakriani Syahrir (DiscoverSys Inc., 2022)
Objective: To explain the correlation between cariogenic (high sugar diet) with Food Neophobia (FN) in Autism Spectrum Disorder (ASD) children. Material and Methods: This type of research is analytically observational with a cross-sectional design. Sampling technique purposive sampling, number of samples 65 respondents of parents/caregivers in LRD community members of suar autism. Data collection with a questionnaire for five eating patterns and FN three questions in the form of a Google Form. The data were analyzed descriptively, and the spearman rank correlation test was used to analyze the difference between diet and FN. Results: Children consume one to two spoons of sugar per day 95.4%; like sweet food 80%, sweet food between meals 80%; soft drinks 49.2%; non-sweet snacks 56.9%. Based on the category of the frequency distribution of neophobia food levels in children with ASD were light 32.31%, moderate 30.77%, and heavy 36.92%. Spearman rank correlation test r=0.06 p>0.05 was 0.36%. Conclusion: This research shows that diet pattern has a very low association with FN in children with autism spectrum disease.